PENGARUH KEMACETAN DI SIMPANG SABILILLAH TERHADAP IMPLEMENTASI CITRA LALU LINTAS DI SIMPANG PROGRESIF - Supiyono, Dwi Ratnaningsih, Rudy Ariyanto (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
Progress of a country in line with the progress of traffic (transport). Fluency in traffic is determined by the smoothness of traffic on the road. Problems often arise on the highway is congestion at the intersection. Neither was signalized intersections and signalized intersections. Problems at the intersection is less accuracy green flame at the intersection with the number of vehicles in a segment. A road with high traffic volume vehicle green flame low while other road traffic volume small green flame length. So in a long queue roads, while other roads are deserted while still green flame. This study aims to minimize the occurrence of conflic at the intersection of green flame. Research will make iterations in the intersection, where a road section which will be nominated densely green flame, the flame of the green according to the volume of traffic on these roads. Each road will be a green flame in accordance with the volume of traffic, without having to change any program there is a change in traffic volume.The degree of saturation of the calculation obtained by ....Keywords: roads, hight traffic, progressive intersection, degree saturation